Cultural differences in teacher immediacy and classroom communication apprehension: an empirical study between Brazil and the United States - Zeneida Parente Alves Neta (Springer, 2024)
Abstract Teacher immediacy and classroom communication apprehension have been well researched in the United States. Instructional communication research in Brazil is limited, and several topics still demand investigation among the population of Brazil. This study extends current research on teacher immediacy and classroom communication apprehension to the Brazilian population. We should extend the analysis to the Brazilian context instead of relying on previous investigations from other regions as the basis for cross-cultural theorizing. A total of 221 students participated in the survey. This study reports four significant findings: (1) Brazilian students' perceptions of teacher immediacy are greater than American students' perceptions of teacher immediacy; (2) American students have higher levels of Classroom Communication Apprehension than Brazilian students; (3) Classroom communication apprehension is negatively correlated with American students' perceptions of teacher immediacy; and (4) Classroom communication apprehension is not significantly correlated with Brazilian students' perceptions of teacher immediacy. Highly immediate teachers will have less apprehensive students.